2010
DOI: 10.1021/nn101390x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Graphene and Graphene Oxide Nanowalls Against Bacteria

Abstract: Bacterial toxicity of graphene nanosheets in the form of graphene nanowalls deposited on stainless steel substrates was investigated for both gram-positive and gram-negative models of bacteria. The graphene oxide nanowalls were obtained by electrophoretic deposition of Mg(2+)-graphene oxide nanosheets synthesized by a chemical exfoliation method. On the basis of measuring the efflux of cytoplasmic materials of the bacteria, it was found that the cell membrane damage of the bacteria caused by direct contact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

76
1,707
4
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,347 publications
(1,791 citation statements)
references
References 58 publications
76
1,707
4
4
Order By: Relevance
“…In general, bacterial deactivation can be the result of: 1) direct mechanical breakage of outer cell membranes by sharp edged nanoparticles (Akhavan and Ghaderi, 2010;Liu et al, 2009;Situ and Samia, 2014); 2) chemical oxidative stress mediated cell injury that is induced by in situ production of reactive oxygen species (Krishnamoorthy et al, 2012;Su et al, 2009); and 3) dehydration of cell membrane (Beney et al, 2004). It is highly likely that the latter two bacterial deactivation mechanisms are at play when wastewater is exposed to Fe 3+ -saturated montmorillonite.…”
Section: Spectroscopy Evidence Of Bacterial Cell Deactivation On Fe 3mentioning
confidence: 99%
“…In general, bacterial deactivation can be the result of: 1) direct mechanical breakage of outer cell membranes by sharp edged nanoparticles (Akhavan and Ghaderi, 2010;Liu et al, 2009;Situ and Samia, 2014); 2) chemical oxidative stress mediated cell injury that is induced by in situ production of reactive oxygen species (Krishnamoorthy et al, 2012;Su et al, 2009); and 3) dehydration of cell membrane (Beney et al, 2004). It is highly likely that the latter two bacterial deactivation mechanisms are at play when wastewater is exposed to Fe 3+ -saturated montmorillonite.…”
Section: Spectroscopy Evidence Of Bacterial Cell Deactivation On Fe 3mentioning
confidence: 99%
“…133,232 Akhavan et al showed that the bacterial inactivation was caused by direct contact of the bacteria with the extremely sharp edges of the nanosheets which results in cell membrane damage. This mechanism of bacterial inactivation therefore allows E. coli to be more resistant to graphene materials compared to S. aureus, due to its outer cell membrane.…”
Section: Environmental and Biological Toxicity Of Graphenementioning
confidence: 99%
“…The toxicity of nanotechnologies on microbial is mainly exhibited in growth inhibition, inhibition of cell wall formation, or cell morphological damage, which thus exert an influence on the microbial community. Graphene and grapheme oxide may both lead to cell membrane damage ruptures of gram-negative bacteria (E. coli) and gram-positive bacteria (S. aureus), resulting in leakage of intracellular substances and thus cell death (Akhavan and Ghaderi 2010). Nano TiO 2 and nano ZnO also affect the soil microbial community, reduce the quantity and diversity of microorganisms in soil, and change soil microbial community compositions (Ge et al 2011).…”
Section: Social Risks Of Nanotechnologiesmentioning
confidence: 99%